Age-related dynamics of height of bone system of sapling of sheep of basic breeds of South Ural - V I Kosilov; D A Andrienko; T S Kubatbekov (RUDN Journal of Agronomy and Animal Industries, 2015)
The article presents data and analysis of the dynamics of development of individual parts of the skeleton, half-carcasses of young Tsigal, South Ural and Stavropol breeds in the conditions of the Southern Urals. Comprehensive study of the growth and development of the skeleton in the postnatal ontogenesis will develop methods of purposeful influence on the formation of myasnosti animals by sex, age and breed. The experimental data suggest that infants rams have better development of the skeleton than Mutton, due to sexual dimorphism. Thus, the superiority of the rams Tsigal rock peers on the total weight of the bones at birth was 5 g (1.5%) by weight of the bones of the axial skeleton Division - 2.3 g (1.5%), peripheral - 2.7g (1.5%) in the rock Yuzhnouralskaya this difference in magnitude to the studied parameters rams were respectively 28 g (9.5%), 12.8 g (9.5%) and 15.2 g (9.5%) at Stavropol breed - 15 g (5.3%), 6.8 g (5.3%) and 8.2 g (5.3%). A similar pattern was observed in the subsequent age periods.